Revolutionizing Accounting and Audit with Blockchain Technology: Scientific Literature Review - Khairunnisa Almadany; Rizaldy Khair (Cattleya Darmaya Fortuna, 2023)
Blockchain technology is disrupting traditional practices in accounting and audit fields. This article explores how blockchain's transparency, immutability, and decentralization are reshaping financial transactions and record-keeping. Conventional accounting faces challenges like data accuracy and fraud prevention, which blockchain addresses through an unalterable, decentralized ledger for real-time financial transaction records. Each transaction is securely linked using cryptography, forming a tamper-proof chain that reduces fraud risk and ensures an auditable trail. Blockchain's impact on accounting lies in its ability to automate processes through smart contracts. These self-executing codes enable instant revenue recognition, automated intercompany transactions, and compliance with standards. Blockchain also enhances audit efficiency by granting auditors access to immutable financial data and automating audit procedures. Despite challenges like scalability and privacy, blockchain's transformative potential is evident in real-world applications across sectors. Its implementation demands stakeholder collaboration to navigate technical and ethical considerations. As blockchain evolves, its role in accounting and audit is set to redefine financial transparency and accountability.